2021
DOI: 10.1016/j.celrep.2021.108871
|View full text |Cite
|
Sign up to set email alerts
|

Circuit reorganization in the Drosophila mushroom body calyx accompanies memory consolidation

Abstract: Highlights d Synaptic microglomeruli linked to a specific odor can be identified in Drosophila d Microglomeruli represent complex microcircuits involving different types of neurons d Long-term memory results in increased microglomeruli in an input-specific manner d Newly formed microglomeruli participate in conditioned odor representation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 78 publications
3
48
0
Order By: Relevance
“…Taking advantage of emerging electron microscopy (EM) datasets covering a full adult fly brain (FAFB, (Zheng et al 2018)) or a large fraction of it (Hemibrain, (Scheffer et al 2020)), we examined the distribution of synaptic contacts between APL, PNs and KCs, the major cell types constituting the MGs of the mushroom body calyx (Leiss et al 2009b; Yasuyama, Meinertzhagen, and Schürmann 2002a; Baltruschat et al 2021) (Fig 1A). We recently reconstructed an entire MG in the FAFB dataset, starting from a PN-bouton of the DA1 glomerulus and tracing all its pre- and post-synaptic partners (Baltruschat et al 2021). Here, we focused on the synaptic connections involving APL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of emerging electron microscopy (EM) datasets covering a full adult fly brain (FAFB, (Zheng et al 2018)) or a large fraction of it (Hemibrain, (Scheffer et al 2020)), we examined the distribution of synaptic contacts between APL, PNs and KCs, the major cell types constituting the MGs of the mushroom body calyx (Leiss et al 2009b; Yasuyama, Meinertzhagen, and Schürmann 2002a; Baltruschat et al 2021) (Fig 1A). We recently reconstructed an entire MG in the FAFB dataset, starting from a PN-bouton of the DA1 glomerulus and tracing all its pre- and post-synaptic partners (Baltruschat et al 2021). Here, we focused on the synaptic connections involving APL.…”
Section: Resultsmentioning
confidence: 99%
“…APL is suggested to regulate sparse coding by participating in a closed feedback loop with the MB, similarly to its homolog giant GABAergic neuron (GGN) in the locust (Papadopoulou et al 2011; A. C. Lin et al 2014; Litwin-Kumar et al 2017). However, APL is both pre- and post- synaptic to PNs and KCs in the adult calyx (Yasuyama, Meinertzhagen, and Schürmann 2002b; Wu et al 2013; Baltruschat et al 2021). Additionally, APL response to localized stimuli is spatially restricted (Amin et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…CREB-dependent regulation of gene expression in DAL neurons appears sufficient to promote systems memory consolidation by modulating neural excitability. Further studies may elucidate whether neural circuits involved in motivation and attention also modulate DAL neurons during LTM formation ( 25 , 26 ) and whether such prolonged neural activity also produces synaptic plasticity in DAL neurons ( 19 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The microglomeruli that form as projection neurons from the antennal lobe connecting to the Kenyon cell dendrites at the calyx are also modified by experience. After conditioning young flies with an odorant (11- cis -vaccenylacetate) to form long-term memory, the size of the microglomeruli responding to this odorant decreased, but the number of such microglomeruli increased ( Baltruschat et al, 2021 ). This demonstrated that new synaptic boutons are formed during learning and for long-term memory and that structural change is linked to brain function.…”
Section: Structural Plasticity and Homeostasis In The Adult Drosophila Brainmentioning
confidence: 99%
“…It was recently shown that rut, which encodes Ca 2+ /CaM-dependent adenyl cyclase, is also required for structural plasticity at the calyx. In fact, long-term memory modifies the size and number of microglomeruli in the calyx, but this effect was abolished in rut mutants or by blocking protein synthesis ( Baltruschat et al, 2021 ). Thus, cAMP regulates plasticity in calyx but not the visual system, which means that distinct molecular pathways may underlie structural plasticity in distinct brain regions ( Barth and Heisenberg, 1997 ).…”
Section: Molecular Mechanisms Of Structural Brain Plasticitymentioning
confidence: 99%